2018
DOI: 10.1186/s12913-018-3457-3
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to effective communication between family physicians and patients in walk-in centre setting in Dubai: a cross-sectional survey

Abstract: BackgroundEffective communication between family physicians and their patients is crucial to improving healthcare outcomes and patients’ satisfaction. However, the barriers to effective communication have been weakly studied in the Gulf region with no reported studies in Dubai. This study aims to identify the main perceived barriers to effective communication between patients and their family physicians in Dubai from both the physicians’ and the patients’ viewpoints.MethodsThe study was conducted at 12 primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…al, revealed several issues related to the patient-physician relationship such as lack of time and training, the role of insurance companies, the incentive structure, and lack of support for physicians [ 14 ]. Another study investigating the barriers to communication between family physicians and patients in Dubai showed that female patients experience more time limitations during consultation where not all their issues are addressed as compared to their male counterparts [ 15 ]. That said, gender is known as an important variable for communication styles, decision-making styles, values, and preferences [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…al, revealed several issues related to the patient-physician relationship such as lack of time and training, the role of insurance companies, the incentive structure, and lack of support for physicians [ 14 ]. Another study investigating the barriers to communication between family physicians and patients in Dubai showed that female patients experience more time limitations during consultation where not all their issues are addressed as compared to their male counterparts [ 15 ]. That said, gender is known as an important variable for communication styles, decision-making styles, values, and preferences [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents may experience introspection feelings and anxiety, which could potentially compromise their ability to express feelings and communicate with others [1][2][3]. Thus, one of the major challenges in the dental care of adolescent patients lies in the patient-professional communication and dental anxiety control, since adolescents may not accept children's behavioural techniques anymore nor want to be treated as adults [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Systematic reviews on the effects of interventions to promote patient-centeredness or better interactions with patients have found strong evidence for increased patient-centeredness in encounters and moderate evidence for increased patient satisfaction, 14,15 increased patient adherence, better quality of life, and decreased depression. 15 Another systematic review assessed the effect of interventions on patient empowerment 1 Postgraduate Program in Medical Sciences, Federal University of Santa Catarina, Brazil 2 Hospital Universitário Professor Polydoro Ernani de Sa ˜o Thiago, Florianópolis, State of Santa Catarina, Brazil 3 Center for Exact Sciences and Technology, Federal University of Sergipe, Brazil and found that more successful interventions included training for establishing goals and/or planning actions. 16 Communicating with patients in intensive care units (ICUs) and their families poses challenges, as the environment may be frightening, and patients are usually admitted due to serious, sometimes unexpected, illnesses and injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Doctor-patient communication is essential in healthcare, and it influences care outcomes. 1 When effective, it results in stronger physician-patient rapport, greater patient trust and satisfaction with physicians, better understanding of illness, and more engagement in decision-making and therapeutic planning. 2,3 These result in greater patient autonomy, enablement for self-care, and treatment adherence.…”
Section: Introductionmentioning
confidence: 99%